Behavior of hybrid spinach 424 grown under two protected cultivation systems (Semiárida, 2020)
Spinach (Spinacea oleracea L.), is an important species among the leaf vegetable crops, and one of the most common winter crops developed by growers in the semi-arid region of the pampas, either in greenhouses or directly in the fields. As a plant of cold temperate climate, it can stand low temperatures of up to - 5° C. In our region temperatures can still be lower, influencing the stage of major development of the plant, what makes it necessary to counterbalance the effect of frost, resorting to protected cultivation systems. The aim of this work was to analyze and assess the behavior of two protected cultivation systems in the fields, and their response in terms of production. Two protected cultivation techniques were contrasted, namely polyethylene tunnels (T1) and thermal cover (T2) with a control crop without protection (T0). The experiment was carried out in the vegetable garden of the Faculty of Agronomy, National University of La Pampa using a randomized block design with 3 treatments and 4 replications. The plots, 5 m. long and 0.50 m. between rows, were seeded with a Hybrid 424 on April 15* 2003, using a row-crop seeder of vertical plate. Thinning was performed twenty days after sowing; spacing between plants was 0.10 m. on the sowing line, with a density of 20 plants.m2 After emergence, all treatments were fertilized with 100 Kg.ha-1 urea. The harvest for treatments T1 and T2 was on July 7th 2003 and for T0 on July 30* 2003. ANOVA, performed according to Tukey's Test, showed significant differences in T1 and T2 with respect to T0. no differences were observed between T1 and T2 The current values in which the spinach is commercialized, it makes it very profitable cultivated in both systems of protection. The high prices obtained by this vegetable are due to the distance with regard to producing traditional zones.
Keywords: Spinacea oleracea L.; thermal cover; polyethylene tunnels; transparent polyethylene